Inkonsistensi Hukum - Syamsul Bahri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Since validly enacted Qanun Aceh No.6 on Jinayah Law 2014, there have been three convicted non-Muslims convicted in public. This article will analyze the whipping sentences against non-mulism listed in the qanun. This study is based on the textual qanun and compares with other legislation, such as Law No. 11 of 2006 on the Government of Aceh (Undang-Undang No. 11 tahun 2006 tentang Pemerintahan Aceh), and Law No. 44 of 1999 on the Implementation of Special Features of Aceh Province (Undang-undang No. 44 Tahun 1999 tentang Penyelenggaraan Keistimewaan Propinsi Daerah Istimewa Aceh). The results of the study indicate that the articles related to the caning of non-Muslims in Aceh Qanun No. 6, there is still a multi-interpretive gap, and is controversial, especially when compared to Article 126 paragraphs (1) and (2), section 127 paragraph (2), Law No. 11 of 2006, and Law No.44 of 1999. After examining the points of the article, one legal product with the other appears inconsistent. Besides, it is not appropriate for non-Muslims to be punished, given that the caning is derived from the normativity of Islam, which is different from non-Muslim religion.